2020
DOI: 10.3389/fonc.2020.604214
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in Africa: Is It a Genetic or Environmental Health Problem?

Abstract: Patients of African ancestry have the poorest outcome and the shortest survival rates from cancer globally. This could be attributed to many variables including racial, biological, socioeconomic and sociocultural factors (either single, multiple or combined), which may be responsible for this major health problem. We sought to assess the most common types of cancer that endanger the health of the African people, and tried to investigate the real differences between African and other Non-African patients regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 68 publications
0
35
1
Order By: Relevance
“…This gives a good explaination why the South Asian population usually has low cancer incidence rate (Tran et al 2018). Our findings that varied cancer driver genes are under different selection pressures in different populations can thus help explain geographical disparities of cancer incidence rates, although other factors such as environmental conditions and living styles are also important (Bahnassy et al 2020). These results again, suggest that recent positive selection is a major force driving the evolution of cancer in humans.…”
Section: Discussionmentioning
confidence: 63%
“…This gives a good explaination why the South Asian population usually has low cancer incidence rate (Tran et al 2018). Our findings that varied cancer driver genes are under different selection pressures in different populations can thus help explain geographical disparities of cancer incidence rates, although other factors such as environmental conditions and living styles are also important (Bahnassy et al 2020). These results again, suggest that recent positive selection is a major force driving the evolution of cancer in humans.…”
Section: Discussionmentioning
confidence: 63%
“…[22,29] Most of the extrapolations for lung cancer risk factors for the African population are based on studies conducted among black sub-populations resident in western countries. [13,[30][31][32][33] The many genetic and environmental factors that are associated with increased susceptibility to lung malignancy include but are not limited to tobacco, exposure to outdoor air pollution, diets, and pre-existing lung disease. [13,34,35] Furthermore, these risks were observed to have ethnic and racial predilections.…”
Section: Risk Factors and Prevalence In Africamentioning
confidence: 99%
“…[35,36] In Africa, there is evidence of regional disparities in available literatures on risk factors for lung malignancy. [22,30,33] However, recent genealogical susceptibility studies conducted outside Africa [31,32,37,38] among people of African descent, to determine genetic ancestry and atavism contributing to higher lung malignancy prevalence and poorer outcome and survivorship, examined mutations, and alterations of angiogenic pathway genes such as epidermal growth factor receptor (EGFR) and matrix metalloproteinase-3 (MMP-3) receptor; both of which are commonly associated with higher risk of lung cancer development and poorer prognosis as well as other commonly reviewed lung cancer receptor genes such as tyrosine kinase/Ras/Raf pathway and KRAS; but found no definite or significant association especially among Africans of West African ancestry. Majority of indigenous African genetic susceptibility studies on lung cancer have origins in North Africa with a few from South Africa and none from Nigeria and the rest of West Africa.…”
Section: Risk Factors and Prevalence In Africamentioning
confidence: 99%
“…Globally, Australia tops the list of countries with the highest number of cancer rates, followed by New Zealand and Ireland [ 7 ]. Recently, studies have found that developing countries, in particular those in Africa, are facing an increasing incidence of cancer [ 8 ]. This is attributed to the aging and growth of the population as well as increased occurrence of risk factors linked with economic transition, including physical inactivity, obesity, reproductive behaviors and smoking [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies have found that developing countries, in particular those in Africa, are facing an increasing incidence of cancer [ 8 ]. This is attributed to the aging and growth of the population as well as increased occurrence of risk factors linked with economic transition, including physical inactivity, obesity, reproductive behaviors and smoking [ 8 ]. In South Africa, there were about 108,168 new cancer cases and 56,802 deaths in 2020 among all ages [ 9 ].…”
Section: Introductionmentioning
confidence: 99%